СOMPARATIVE ANALYSIS OF 10-YEAR RESULTS OF TREATMENT EFFICACY IN PATIENTS WITH COLORECTAL CARCINOMA - R. A. Murashko; A. G. Baryshev; L. G. Teslenko; L. L. Stepanova; I. Yu. Lakomsky (Кубанский научный медицинский вестник, 2018)
Aim. To study the dynamics of survival of patients with colorectal cancer in the Krasnodar region for the period of 2006-2015Materials and methods. Patients are divided into groups: registered in 2006, 2009, 2012, 2015. According to the Regional Population Cancer Registry, a comparative analysis of the long-term outcome of treatment of 9,741 patients was conducted by groups.Results. In patients with newly diagnosed colorectal cancer for the past 10 years, a significant increase in the three-year observed, as well as a three-year and five-year adjusted survival rate over the entire follow-up period, was obtained. For all stages of the disease and overall, the observed and adjusted survival rates declined for the first four years after the diagnosis was established, this result was most significant in patients with stage III and IV cancer. An unfavorable prognosis of survival was obtained in patients with stage IV: one-third survive less than a third of patients, the five-year life expectancy in this group was 9.8%.Conclusion. Improving the survival rates of patients with colorectal carcinoma indicates an increase in the effectiveness of providing specialized care for patients with colorectal cancer in the region